Fatalities related to sudden meteorological events across Central Europe from 2010 to 2020. (1st April 2023) - Pilorz, Wojciech; Laskowski, Igor; Surowiecki, Artur; Łupikasza, Ewa
Abstract: Under current climate change, severe weather impacts human life in Central Europe, which is a relatively safe climate zone concerning the occurrence of the most violent weather events. This impact is projected to increase due to ongoing climate change. Therefore, this study, for the first time, discusses the death toll related to selected sudden severe weather phenomena in Central Europe in the 2010–2020 period with particular attention put to the death circumstances caused by the severe weather fatality, and their spatial and temporal distribution. In this study, severe wind, severe rainfall, lightning strikes, tornadoes and avalanches are considered. The data on phenomena occurrence were taken from the verified European Severe Weather Database. The study revealed that an average of 73 people died per year, and 365 people were hurt annually due to severe weather in the study period. Avalanches were found to be the deadliest phenomena, followed by severe wind, lightning and heavy rain. The majority of victims were killed during outdoor activities, such as spending free time outside or driving; however, the dominating death circumstances varied within the analysed domain and were different than those in the other regions of the world. This findings should be taken into account while creating national early-warning systems and better gathering severe weather impact data. Education and raising society awareness according to our results should be implemented as well. Highlights: Detailed circumstances of the fatalities caused by sudden meteorological events have been investigated for the Central Europe. Research revealed some regional differences in the occurrence of the death circumstances. The highest number of fatalities was caused by avalanches (mostly off-piste skiers) and severe wind (mostly drivers). Flood and tornado fatalities are significantly less frequent in Central Europe than in the other regions of the world. Flood fatalities are clearly older than the victims of other phenomena.